Apoptotic Extracellular Vesicles Derived from Human Umbilical Vein Endothelial Cells Promote Skin Repair by Enhancing Angiogenesis: From Death to Regeneration - Liu J; Dong J; Pei X (International Journal of Nanomedicine, 2024)
Jinzhao Liu,1,2,* Jia Dong,1,* Xibo Pei1,2 1State Key Laboratory of Oral Diseases & National Center for Stomatology & National Clinical Research Center for Oral Diseases, West China Hospital of Stomatology, Sichuan University, Chengdu, Sichuan, 610041, People’s Republic of China; 2Department of Prosthodontics, West China Hospital of Stomatology, Sichuan University, Chengdu, Sichuan, 610041, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jia Dong; Xibo Pei, Email scu2013dongjia@sina.com; xbpei@hotmail.comPurpose: The promotion of angiogenesis is an effective strategy for skin wound repair. While the transplantation of endothelial cells has shown promise in vascularization, the underlying mechanism remains unclear. Recent studies have suggested that transplanted cells undergo apoptosis in a short period and release apoptotic extracellular vesicles (ApoEVs) that may have therapeutic potential.Methods: In this study, we isolated ApoEVs from human umbilical vein endothelial cells (HUVECs) and characterized their properties. In vitro, we assessed the effects of ApoEVs on the proliferation, migration, and differentiation of endothelial cells and fibroblasts. In vivo, we investigated the therapeutic role of ApoEVs-AT in full-thickness skin wounds, evaluating wound closure rate, re-epithelialization, granulation tissue formation, vascularization, scar area, and collagen 3(Col3)/collagen 1(Col 1) ratio.Results: ApoEVs derived from HUVECs displayed typical characteristics. In vitro, ApoEVs significantly enhanced the proliferation, migration, tube formation, and expression of angiogenic-related genes in endothelial cells and slightly promoted the proliferation and migration of fibroblasts. In vivo, ApoEVs improved the wound closure rate, re-epithelialization, the formation of granulation tissue, and vascularization. Besides, ApoEVs reduced scar formation, accompanied by an increase in the Col 3/ Col 1 ratio.Conclusion: Given their abundant source and effectiveness, this study provided a novel approach for angiogenesis in tissue regeneration and deepened the understanding of from death to regeneration.Keywords: apoptotic extracellular vesicles, human umbilical vein endothelial cells, skin regeneration, angiogenesis